Nigerian Foreign Policy 60 Years After Independence - Tar, Usman A.; Wapmuk, Sharkdam (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
'This is a timely contribution that responds to the concerns of a renowned political scientist, Joseph Nye, who expressed deep concern about the widening gap between academic theory and foreign policy practice.' -Professor Eghosa Osaghae, Director-General, Nigerian Institute of International Affairs (NIIA) 'The book is a welcome addition and deserves a distinct place among the many academic works on Nigeria's foreign policy. The rich insights by authors carefully selected to contribute to this book will be useful for both academics and policy makers with deep interest in the area of Nigeria's foreign policy architecture. -Otunba Olusegun Akinsanya, mni, Former Ambassador of the Federal Republic of Nigeria to Ethiopia 'A timely work of scholarship devoid of propaganda offering a rich mix of optimism and criticism of Nigeria's foreign policy in the past 60 years.' -Ambassador Zango Abdu, mni, Retired Diplomat This book covers critical issues in Nigeria's external relations since 1960. As an independent nation, Nigeria has stood out as the most populous black country in the world and contributed immensely to the search for solutions to pressing international issues, notably in Africa affairs. Nigeria has also participated actively in global affairs and used the platform of international organisation to advance her national interests, cognisant also of its regional and global obligations and responsibilities. Contributors to this thought-provoking book make a strong case for Nigeria to press for a foreign policy that puts Nigerian people at the centre. One of the strong points also emanating from the contributors of this book is the imperative for Nigeria to address domestic challenges that continue to impinge on the country's external image. Usman A. Tar is Endowed Professor of Defence and Security Studies, and Dean of the Faculty of Arts and Social Sciences at the Nigerian Defence Academy. Sharkdam Wapmuk is Associate Professor at the Department of Defence and Security Studies, Nigerian Defence Academy.
Part 1: Introduction -- Chapter 1: Introduction: understanding Nigeria's foreign policy: reflections on Nigeria's journey so far -- Part 2: The domestic dimensions of Nigeria's foreign policy and external relations -- Chapter 2: Bureaucratic model: the ministry of foreign affairs and Nigerian foreign policy -- Chapter 3: Nigerian foreign policy and challenges of economic development -- Part 3: Afrocentricity and the regional dimensions of Nigeria's foreign policy -- Chapter 4: A critical review of Nigeria's Afrocentric policy: rationale, gains and consequence -- Chapter 5: Natural resource endowment and regional integration in west Africa: the setbacks and implications for Nigerian foreign policy -- Part 4: Nigeria and the global and emerging powers -- Chapter 6: The dynamics and strategic interests in Nigeria-US relations -- Chapter 7: Nigeria-UK relations in the 21st century -- Chapter 8: The foreign policy of emerging big power? Nigeria and china's belt and road initiative -- Chapter 9: Nigeria-South Africa relations: prospects and challenges of a strategic partnership -- Chapter 10: Nigeria-Brazil relations: ties that bind and binds that tie -- Part 5: Contemporary issues and challenges in Nigeria's foreign policy environment -- Chapter 11: Nigeria's foreign policy since independence: problems, challenges and opportunities -- Chapter 12: Nigeria foreign policy in the age of globalization: issues and challenges -- Chapter 13: "Gulliver's Odyssey": assessing Nigeria's role in Ecowas -- Chapter 14: Migration and Nigeria's external relations: a trend analysis of its nature and dynamics in the last 60 years -- Chapter 15: Nigeria's foreign policy and diaspora engagements: the unharnessed strategic asset -- Chapter 16: Climate change and Nigeria's foreign relations -- Chapter 17: Nigeria relations with the organisation of Islamic countries -- Part 6: Conclusion -- Chapter 18: Conclusion: future prospects of Nigeria's foreign policy beyond 60 years of independence: emerging trends and tasks ahead.
Keywords: International relations; Political science; Diplomacy; Security, International; Comparative government; Africa -- Politics and government; Foreign Policy; Governance and Government; Diplomacy; International Security Studies; Comparative Politics; African Politics